The effect of mobile phone text message reminders on health workers’ adherence to case management guidelines for malaria and other diseases in Malawi: lessons from qualitative data from a cluster-randomized trial - Kaunda-Khangamwa, B; Steinhardt, L; Rowe, A; Gumbo, A; Moyo, D; Nsona, H; Troell, P; Zurovac, D; Mathanga, D (BioMed Central, 2018)
Background Mobile health (mHealth), which uses technology such as mobile phones to improve patient health and health care delivery, is increasingly being tested as an intervention to promote health worker (HW) performance. This study assessed the effect of short messaging services (SMS) reminders in a study setting. Following a trial of text-message reminders to HWs to improve case management of malaria and other childhood diseases in southern Malawi that showed little effect, qualitative data was collected to explore the reasons why the intervention was ineffective and describe lessons learned. Methods Qualitative data collection was undertaken to lend insight into quantitative results from a trial in which 105 health facilities were randomized to three arms: (1) twice-daily text-message reminders to HWs, including clinicians and drug dispensers, on case management of malaria; (2) twice-daily text-message reminders to HWs on case management of malaria, pneumonia and diarrhoea; and, (3) a control arm. In-depth interviews were conducted with 50 HWs in the intervention arms across seven districts. HWs were asked about acceptability and feasibility of the text-messaging intervention and its perceived impact on recommended case management. The interviews were recorded, transcribed and translated into English for a thematic and framework analysis. Nvivo 11 software was used for data management and analysis. Results A total of 50 HWs were interviewed at 22 facilities. HWs expressed high acceptance of text-message reminders and appreciated messages as job aids and practical reference material for their day-to-day work. However, HWs said that health systems barriers, including very high outpatient workload, commodity stock-outs, and lack of supportive supervision and financial incentives demotivated them, limited their ability to act on messages and therefore adherence to case management guidelines. Drug dispensers were more likely than clinicians to report usage of text-message reminders. Despite these challenges, nearly all HWs expressed a desire for a longer duration of the SMS intervention. Conclusions Text-message reminders to HWs can provide a platform to improve understanding of treatment guidelines and case management decision-making skills, but might not improve actual adherence to guidelines. More interaction, for example through targeted supervision or two-way technology communication, might be an essential intervention component to help address structural barriers and facilitate improved clinical practice.